Paradigm Shift for Online Learning: Voices of Undergraduates from a National University in Sri Lanka - L A P Madhuwanthi; Aruna Muthulingam; M G H Madusha (International Journal of Education, Teaching, and Social Sciences, 2021)
The abrupt eruption of the Covid-19 pandemic made drastic shifts in doing many things under new normal conditions. Consequently, the education sector too had a giant leap from traditional physical mode to an online learning method, giving a novel experience to students. Online learning is a form of education in which the main elements include the physical separation of teachers and students during instruction and the use of various technologies to facilitate student-teacher and student-student communication. Hence, this paper focuses on exploring problems faced by undergraduates in online learning in a national university in Sri Lanka. This is a qualitative study that used a convenient sample of 30 undergraduates who have undergone both the traditional learning mode and online learning method. Data collection was carried out through a self-administered, semi-structured questionnaire and thematic analysis was employed for the study. The study found that undergraduates are experiencing variety of problems in online learning as; technical issues, absence of conducive learning environment, financial burden, issues encountered from lecturers, pedagogical issues, and personal issues. This study provides useful implications for both the education policy formulators and educational institutions for the improvement of their online learning methods.